Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kedisplinan dan Kinerja Guru di SMPN 1 Mambi Kabupaten Mamasa - Tatiek Ary Santi; Muhammad Yunus; Hafipah (STIM-LPI Makassar, 2023)
The aims of this study were 1) to analyze the influence of the principal's leadership on discipline at SMP Negeri 1 Mambi, Mamasa Regency, 2) to analyze the influence of the principal's leadership on teacher performance at SMP Negeri 1 Mambi, Mamasa Regency, 3) to analyze the effect of discipline on teacher performance at SMP Negeri 1 Mambi, Mamasa Regency, and 4) to analyze the influence of the principal's leadership on teacher performance through discipline at SMP Negeri 1 Mambi, Mamasa Regency. The analytical method used in this research is path analysis method. The research data were obtained from 38 teachers at SMP Negeri 1 Mambi, Mamasa Regency. The research approach is a causal approach that is explanatory in nature. The results of this study indicate that: 1) The principal's leadership has a positive and significant effect on discipline, this means that the principal's leadership can improve teacher discipline at SMP Negeri 1 Mambi Mamasa Regency, 2) Principal leadership has a positive and significant effect on teacher performance, p. this means that the principal's leadership can improve teacher performance at SMP Negeri 1 Mambi, Mamasa Regency, 3) Discipline has a positive and significant effect on teacher performance, this means that discipline can improve teacher performance at SMP Negeri 1 Mambi Mamasa Regency, and 4) Principal leadership has a positive and significant effect on teacher performance through discipline, this means school principal leadership can improve performance teachers through teacher discipline at SMP Negeri 1 Mambi, Mamasa Regency.